EVALUASI KEMAMPUAN LAHAN DESA LUMBAN LOBU KECAMATAN BONATUA LUNASI KABUPATEN TOBA SAMOSIR - Sembiring, Bintang Mariani; Lynneus, Julpan (JURNAL AGRICA, 2015)
The land capability evaluation on Lumban Lobu Village Toba Samosir Distric was conducted in April-Juli 2011. The purpose of this study was to determine the land capability class on Lumban Lobu Village Toba Samosir Distric with the method of inhibiting factors and matching according to the land capability class by Arsyad (2006). Analysis of the soil included soil texture, permeabilty, bulk density, salinity and soil organic matter. The research conducted in Research and Technology Laboratory, Agriculture Faculty of North Sumatera University. The field observation entrust for slope, erosion, depth of soil, drainage, gravel/rock and the flooding/inundation. The results showed that area Lumban Lobu has actual land capability Class III (es), The land in these class III can be used for the crops and forest productions, es mean there are  inhibiting factor on erosion and the depth of the root zone or soil. Erosion factor can be improve, thus on Lumban Lobu Village the land capability could be potential for the Class III (s). Key words: land evaluation, land capability